2021
DOI: 10.3389/fcvm.2021.713021
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Mesenchymal Stem Cell Derived Exosomes Delivered Using Silk Fibroin and Sericin Composite Hydrogel Promote Wound Healing

Abstract: Recent studies have shown that the hydrogels formed by composite biomaterials are better choice than hydrogels formed by single biomaterial for tissue repair. We explored the feasibility of the composite hydrogel formed by silk fibroin (SF) and silk sericin (SS) in tissue repair for the excellent mechanical properties of SF, and cell adhesion and biocompatible properties of SS. In our study, the SF SS hydrogel was formed by SF and SS protein with separate extraction method (LiBr dissolution for SF and hot alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 73 publications
(92 reference statements)
0
10
0
Order By: Relevance
“…The results proved notably suppressed inflammation in AT, the proliferation of tendon cells, and prevented extracellular matrix degradation (Fig. 7) [88]. Additionally, MN patch promoted cell migration and angiogenesis by slowly releasing MSCs derived exosomes and penetrating into the deep layer of the skin, presenting a potentially valuable method for repairing diabetic wound in clinical applications [90].…”
Section: Exosomes With New Dosage Formmentioning
confidence: 89%
“…The results proved notably suppressed inflammation in AT, the proliferation of tendon cells, and prevented extracellular matrix degradation (Fig. 7) [88]. Additionally, MN patch promoted cell migration and angiogenesis by slowly releasing MSCs derived exosomes and penetrating into the deep layer of the skin, presenting a potentially valuable method for repairing diabetic wound in clinical applications [90].…”
Section: Exosomes With New Dosage Formmentioning
confidence: 89%
“…It was shown that silk fibroin (SF) had excellent mechanical properties and silk sericin (SS) induced adhesion and biocompatibility. Human umbilical cord blood MSC-derived exosomes encapsulated in SF-SS hydrogels promoted nerve growth and suppressed the inflammatory response ( Han et al, 2021 ), and we speculate that they have potential in SCI repair.…”
Section: Exosomes Combined With Biomaterials Scaffolds In Spinal Cord...mentioning
confidence: 98%
“…Another study explored the feasibility of a composite hydrogel formed from silk fibroin (SF) and silk sericin (SS) due to the excellent mechanical properties of SF, and the cell-adhesion and biocompatibility properties of SS. After encapsulating and delivering UMSC-Exos, SF–SS hydrogels promoted wound healing and angiogenesis [ 130 ]. Additionally, the delivery of platelet-rich plasma exosomes in a composite chitosan–silk hydrogel sponge was found to upregulate collagen synthesis and deposition, as well as angiogenesis, at the wound site in diabetic rat models [ 127 ].…”
Section: Biomedical Exploitation Of Exosomes Delivered In Hydrogelsmentioning
confidence: 99%